Weed Control in Okra - William M. Stall (EDIS)
Revised! HS-192, a 2-page fact sheet by William M. Stall, provides pesticide recommendations for okra production. Includes a table listing chemical weed controls for okra in Florida. Published by the UF Department of Horticultural Sciences, November 2007.